Wind-structure interaction mechanism of circular storage shells- a critical review - Mukherjee, Soumya; Singha Roy, Dilip Kumar (Mechanics of advanced materials and structures, 2024)
A critical review on the valuable researches about the aerodynamic load and consequent structural behavior of cylindrical storage shells, has been carried out. The wind-shell interaction mechanism has been explored through literatures to understand aerodynamic pressure characteristics, wind-induced vibration, buckling and design of cylindrical storage shell and stiffener. Important input parameters have been presented in a tabulated manner so as to correlate and compare critical output parameters (graphically) with an emphasis on circumferential wind pressure coefficient and radial deflection per unit thickness under wind-induced buckling. The scopes for future studies in this field of research have also been recommended.